Arah Metodologi Tafsir Kontemporer - Niila Khoiru Amaliya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2018)
Methods of interpretation evolve over time. This is because the problems of human life that need to refer to the Qur‟an is constantly evolving, while Qur‟anis definite and static, there is no development in its verses as well as in human life‟s problems. Therefore, an interpretation is sometimes considered moreappropriate at a certain period and not at another. Various methods of interpretation have been offered in the history of Muslims such as method oftahlili, ijmali, muqaran also maudlui. These methods have helped human to understand Qur‟an. Nowadays, maudlu‟i becomes the most frequently methodused by Muslims. Thus, this paper tries to find the direction of current interpretive methodology. This can be seen in the tendency of contemporaryinterpretation, which has assumption and paradigm that 1) Qur‟an Shalihlikulli zaman wamakan 2) Text is static while context is dynamic 3) Interpretation isrelative and tentative. With its character of paradigm that 1) Positioning Qur‟an as a Guide Book, using an interdisciplinary approach 2)Contextual andoriented to the spirit of Qur‟an. The solution of contemporary paradigmis to find alternatives toward Qur‟an bimaqashid al-syari‟ah. 3) Scientific, Critical,Non-Sectarian with the method of interpretation is method of maudlui.